Endoscopically Assisted Management of Bilateral Coronoid Hyperplasia: A Case Report with Oral-Health-Related Quality of Life Outcomes - Juraj Brozović; Igor Čvrljević; Marko Tarle; Barbara Mikulić; Bruno Vidaković; Ivica Lukšić (Journal of Clinical Medicine, 2026)
Background/Objectives: This case report describes a rare case of bilateral coronoid hyperplasia (CPH) with suspected Jacob’s disease in a young female patient, managed by endoscopically assisted coronoidectomy, and provides quantitative oral-health-related quality of life (OHRQoL) and pain outcomes. Methods: An 18-year-old female with severely restricted mouth opening underwent bilateral endoscopically assisted intraoral coronoidectomy. OHRQoL and pain were assessed with the Oral Health Impact Profile 14 (OHIP-CRO14) and a 100 mm visual analogue scale (VAS) preoperatively, daily for seven postoperative days, and at one year. Results: Maximum mouth opening improved from 8 mm to 35 mm at nine months (+338%). OHIP-14 total scores remained within a “poor”-to-“moderate” impact and low quality of life from the preoperative value (38) throughout the postoperative week (31–38) and decreased to 14 at one year (−63%; “good” impact, very high quality of life). Psychological disability and psychological discomfort were the most affected domains. VAS scores rose from 36 preoperatively, peaked at 55 on day 2, fluctuated as mild pain (27–44), and resolved at one year. Conclusions: Endoscopically assisted intraoral coronoidectomy restored functional mouth opening and produced clinically meaningful improvements in pain and OHRQoL, with the largest gains in psychological domains. To the authors’ knowledge, this is the first case report providing quantified, domain-resolved OHRQoL outcomes after coronoidectomy.